Vitamin D insufficiency and deficiency in patients with fractures of the fifth metatarsal. (June 2016) - Clutton, Juliet; Perera, Anthony
Highlights: Isolated fifth metatarsal fractures are almost universally low energy or stress injuries. Hypovitaminosis D is known to be associated with fragility fractures in other areas of the body. Hypovitaminosis D is more common in winter, when Vitamin D cannot be endogenously produced in the UK population. Vitamin D supplementation can aid fracture healing and reduce risk of fragility fractures. Serum vitamin D levels should be checked in patients with fifth metatarsal fractures, and supplemented where necessary. Abstract: Introduction: The fifth metatarsal is a common site for both acute and stress fractures in the foot. They are usually isolated low-energy or stress fractures. Vitamin D deficiency has been associated with fragility fractures in many parts of the body. We believe that low Vitamin D could be a significant aetiological factor in fractures of the fifth metatarsal. Methodology: A prospective study of patients with fractures of the fifth metatarsal was conducted. Patients presenting to fracture clinic with these fractures had their vitamin D and calcium levels measured. We also conducted a literature review of studies of vitamin D levels in the Northern Hemisphere between 1990 and 2014. Results: Forty patients with fifth metatarsal fractures were studied (22 metatarsal base fractures, 6 shaft fractures, and 2 stress fractures). The average patient age was 49 (range 22–83). 12 patients (30%) had a Vitamin D level consistent with deficiency, and a further 14 (35%) had a level consistent with insufficiency. Average Vitamin D levels in winter fractures were significantly lower (52.23 nmol/L) than for those sustained in summer (76.73 nmol/L). Conclusions: Hypovitaminosis D was common in patients with fifth metatarsal fractures. Vitamin D supplementation has been shown in animal studies to improve fracture healing rates, and in humans to decrease the risk of fragility fracture. It should be part of regular practice to check Vitamin D levels in these patients, and supplement where necessary.